Reading for Race and Romance in Imperial Intimacies and The Woman of Colour - Barr, Rebecca (Romanticism on the Net, 2024)
Reading The Woman of Colour in conjunction with Hazel Carby’s Imperial Intimacies exposes the racialized and exclusionary logic of the romance genre. Both works provide ramifying instances of the ways in which romance tropes, plot conventions, and sentimentalist gloss falter when brought to bear on racialized subjects. Following the insights of Margo Hendricks’ Race and Romance: Coloring the Past (2022), the article shows how the failures of romance conventions allow us to glimpse the “fictions of racial logic” (Carby, 61) underpinning the ostensibly universalist pleasures of the romance plot. Carby’s critical fabulation is an invaluable supplement to the novel, catalysing its critical insights. Imperial Intimacies adds historical and theoretical context which resonates with the romantic-era novel, prompting us to think about the recuperative possibilities of storytelling as well as the necessary limits on the works of the imagination. Both are ‘tales’: open-ended works which flaunt their lacunae to better evoke the fractured worlds they represent. Reading Carby’s contemporary work allows readers to better grasp the paradoxes of imperialist desire and the ways in which coercive power structures both conjure and abort The Woman of Colour’s romance narrative.